BS EN 17020-5. Extended application of test results on durability of self-closing for fire resistance and/or smoke control doorsets and openable windows. Part 5. Durability of self-closing of hinged and pivoted timber doorsets (24th June 2021) - British Standards Institution,
No abstract available